JOURNAL OF GOVERNMENT & POLITICS : The Social Media As A Transformative Agent In The Electoral Process - David N. Almarez, DM, Ajree D. Malawani (FISIPOL UMY, 2016)
The growing use of social media in social interaction has changed the mode of political campaign in the Philippines.